Better Outcomes for Older people with Spinal Trouble (BOOST) trial: statistical analysis plan for a randomised controlled trial of a combined physical and psychological intervention for older adults with neurogenic claudication - Marian, IR; Williamson, E; Garrett, A; Lamb, SE; Dutton, SJ (BioMed Central, 2020)
Background Neurogenic claudication is a common spinal condition affecting older adults that has a major effect on mobility and implicitly independence. The effectiveness of conservative interventions in this population is not known. We describe the statistical analysis plan for the Better Outcomes for Older people with Spinal trouble (BOOST) randomised controlled trial.